Applied theatre aesthetics - White, Gareth 1968-; Balfour, Michael; Preston, Sheila (London Bloomsbury Methuen Drama, 2015)
"Applied Theatre: Aesthetics re-examines how the idea of 'the aesthetic' is relevant to performance in social settings. The disinterestedness that traditional aesthetics claims as a key characteristic of art makes little sense when making performances with ordinary people, rooted in their lives and communities, and with personal and social change as its aim. Yet practitioners of applied arts know that their work is not reducible to social work, therapy or education. Reconciling the simultaneous autonomy and heteronomy of art is the problem of aesthetics in applied arts. Gareth White's introductory essay reviews the field, and proposes an interdisciplinary approach that builds on new developments in evolutionary, cognitive and neuro-aesthetics alongside the politics of art. It addresses the complexities of art and the aesthetic as everyday behaviours and responses. The second part of the book is made up of essays from leading experts and new voices in the practice and theory of applied performance, reflecting on the key problematics of applying performance with non-performers. New and innovative practice is described and interrogated, and fresh thinking is introduced in response to perennial problems"--Provided by publisher.
Machine generated contents note: -- Introduction Chapter 1 - Aesthetics and the Aesthetic (Gareth White) Chapter 2 - Aesthetic Autonomy and Heteronomous Aesthetics (Gareth White) Chapter 3 - Dancing With Difference: Moving Towards a New Aesthetics (Nicola Shaughnessy, University of Kent, UK) Chapter 4 - Revolutionary Beauty Out of Homophobic Hate (Mojisola Adebayo, Queen Mary, University of London, UK) Chapter 5 - Competing International Players and their Aesthetic Imperatives:The Future of Internationalised Applied Theatre Practice? (Kirsten Sadeghi-Yekta) Chapter 6 - Aesthetic Play: Between Performance and Justice (Ananda Breed, University of East London, UK) Chapter 7 - The Political Imagination and Contemporary Theatre for Youth (Anna Hickey-Moody, Goldsmiths, University of London, UK) Chapter 8 - The Aesthetics of Becoming; Applied Theatre and the Quest for Cultural Certitude (Brian Heap, University of West Indies)Epilogue (Gareth White)NotesIndex.
Includes bibliographical references (pages 257-300) and index.
Keywords: Theater -- Aesthetics; Theater -- Philosophy